Cenosphere formation and combustion characteristics of single droplets of vacuum residual oils - Setyawan, Hendrix Yulis; Zhu, Mingming (Taylor & Francis, 2025)
The ignition, combustion characteristics, and cenosphere formation of single droplets combustion of four vacuum residues (VRs) from different refineries with various asphaltene contents were studied experimentally. The single droplets of VRs were suspended at the tip of a silicon carbide fiber and heated in air at temperatures of 973 and 1023 K, respectively, in an electrically heated tube furnace. The ignition and combustion behavior of the VRs were recorded using a CCD camera, which enabled the determination of droplet size, ignition delay time, flame duration, and cenosphere size. The effect of initial droplet size, gas temperature, and asphaltene content on the ignition delay time, flame duration, cenosphere morphology, and particle size were investigated. The whole ignition and combustion process of single droplets of the VRs consisted of five stages in succession: (1) pre-ignition, mainly involving the evaporation of highly volatile components from the droplet surface; (2) steady combustion of fuel vapors evaporated from the droplet surface; (3) splashing combustion of fuel vapors evaporated from droplet interior; (4) disruptive combustion due to thermal decomposition of asphaltene; and (5) solid residue ignition and combustion. A visible and sooty flame was formed upon ignition and lasted during stages 2–4. The droplet size increased sharply in the stage 4 due to the thermal decomposition of asphaltene, which was more profound for VRs with higher asphaltene content and at higher gas temperatures. The ignition delay time increased with increasing initial droplet size and gas temperature but varied little as the asphaltene content in the VRs increased, suggesting that the ignition process of VRs was controlled by the vaporization of high volatile components on the droplet surface. The thermal decomposition of asphaltene produced solid residue, which was in the form of a cenosphere with the shell thickness being ca. 20 μm and a number of blowholes presented in the shell. The VRs with higher asphaltene content had more and bigger blowholes. The ratio of cenosphere particle size to initial droplet size is independent of the initial droplet size but almost increased linearly with the asphaltene content in the VRs.
Keywords: Combustion; cenosphere; droplets; ignition; vacuum residue